THE ROLE OF ECOLOGICAL CULTURE IN ENVIRONMENTAL BALANCE (Scientific journal of the Fergana State University, 2025)
Nature can continue its existence without depending on human culture, but human culture cannot exist without nature.This article analyzes the role of ecological knowledge and culture in the process of harmony and interaction between man and nature. In the course of the historical development of humanity, we can witness that the relationship of man to nature has changed dramatically, and the violation of the laws of nature has caused material, spiritual and social crises in all spheres of human life and activity. Therefore, the conclusions of our research require that it is of urgent importance to realize our human duty to the next generation, to take our position as an active member of society, and first of all, to bring the formation of ecological consciousness, knowledge and culture to a higher level.The article contains a number of step-by-step measures aimed at improving environmental knowledge and culture. These events are characterized by the fact that they require efforts that cannot be delayed.